Full-Spectrum Cannabidiol for Treating Chronic Temporomandibular Arthralgia: A Case Report - Tanganeli, Joao Paulo Colesanti; Tanganeli, Marianna Delle Serre [UNESP]; Oliveira, Daniela Fernandes Lobo Molica [UNESP]; Fernandes, Ellen Eduarda [UNESP]; Rode, Sigmar de Mello [UNESP] (Mary Ann Liebert, Inc, 2023)
Introduction: Temporomandibular disorders (TMDs) are public health problem that can considerably affect quality of life. In particular, chronic situations are a challenge for the involved health teams, as they demand care related to central mechanisms and are not always well understood. Since the discovery of the endocannabinoid system and other systems controlled or influenced by it, many studies have reported positive and promising results. Currently, revisions of legislation regarding the use of cannabis and its derivatives in different parts of the world have allowed us to advance scientifically. The treatment of pain using cannabinoid substances can be of great value for the development of drugs that allow significant advancements in the therapy of patients with pain syndromes, particularly in cases of difficult control. Methods: A case of chronic TMD with several previous interventions was presented who was treated with full-spectrum cannabidiol. Treatment period-started December 13, 2021, continuous use. Results: Excellent results and remarkable improvement yielded in the patient's quality of life. Conclusions: Refractory cases can benefit from the use of medicinal cannabis, but further studies are needed to confirm the efficacy and safety of these drugs to long-term treatment.
Keywords: Cannabis sativa; cannabinoids; endocannabinoids; temporomandibular disorders; orofacial pain